Synthesis, characterization and crystal structure of cis-bis[4-fluoro-N-(diethylcarbamothioyl)benzamido-κ2O,S]platinum(II) - Gumus, Ilkay; Solmaz, Ummuhan; Celik, Omer; Binzet, Gun; Balcı, Gulten Kavak; Arslan, Hakan (European Journal of Chemistry, 2015)
cis-Bis[4-fluoro-N-(diethylcarbamothioyl)benzamido-κ2O,S]platinum(II), cis-[Pt(L-O,S)2], was synthesized and characterized by elemental analyses, FT-IR and NMR techniques. The obtained metal complex was also characterized by a single crystal X-ray diffraction study. Molecule formula of the title compound is C24H28F2N4O2PtS2: tetragonal, space group I41/a, a = 19.7530(4) Å, b = 19.7530(4) Å, c = 13.7137(3) Å, V = 5350.83(19) Å3, Z = 8, Dcalc = 1.742 g/mm3, 22890 reflections measured (3.62 ≤ 2Θ ≤ 52.72), 2733 (Rint = 0.0272), which were used in all calculations. A square-planar coordination geometry is formed around the Pt atom by two S atoms and two O atoms of the N-(diethylcarbamothioyl)-4-fluorobenzamide ligand which are a cis configuration.